2008
DOI: 10.1111/j.1365-2494.2008.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantities of mineral N in soil and concentrations of nitrate‐N in groundwater in four grassland‐based systems of dairy production on a clay‐loam soil in a moist temperate climate

Abstract: This study examined the quantity of mineral N in soil and nitrate-N losses to groundwater from grasslandbased dairy production in 2001 and 2002. There were four treatments with different inputs of N, through fertilizers, concentrates and biological fixation, and four associated stocking densities. Nitrogen inputs were 205, 230, 300 and 400 kg ha )1 , respectively, and annual stocking densities were 1AE75, 2AE10, 2AE50 and 2AE50 cows ha )1 . There were 18 cows per treatment. Grazed herbage accounted for 0AE64, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…In addition, the spatial (Peck et al, 1977;Gumiere et al, 2013) and temporal variability (Mapa et al, 1986;Sousa et al, 2013) of weather and soil data and the proximity of a particular landscape position relative to ground and surface water receptors (Jordan et al, 2005;Schulte et al, 2006;Fenton et al, 2008;Fenton et al, 2011;Sousa et al, 2013) are significant when determining the importance of t u . Numerous studies (Foussereau et al, 2001;Baily et al, 2011;Fenton et al, 2011;Gladnyeva and Saifadeen, 2013;Huebsch et al, 2013;Premrov et al, 2014) have identified the critical influence exerted by meteorological patterns on t u .…”
Section: Time Lagmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the spatial (Peck et al, 1977;Gumiere et al, 2013) and temporal variability (Mapa et al, 1986;Sousa et al, 2013) of weather and soil data and the proximity of a particular landscape position relative to ground and surface water receptors (Jordan et al, 2005;Schulte et al, 2006;Fenton et al, 2008;Fenton et al, 2011;Sousa et al, 2013) are significant when determining the importance of t u . Numerous studies (Foussereau et al, 2001;Baily et al, 2011;Fenton et al, 2011;Gladnyeva and Saifadeen, 2013;Huebsch et al, 2013;Premrov et al, 2014) have identified the critical influence exerted by meteorological patterns on t u .…”
Section: Time Lagmentioning
confidence: 99%
“…Such a limitation has been well documented in the literature (Chiu and Shackleford, 1998;Vereeken et al, 2010). However, it is reasonable to assume that in such 'heavy' soils (which represent 32% of Irish agricultural soils; Humphreys et al, 2008), or those soils possessing a low permeability layer at shallow depth (e.g. due to natural or anthropogenic reasons), mixed contaminant nutrient losses to a surface waterbody are more likely to occur through overland flow rather than sub-surface pathways (Kurz et al, 2005 a/b;Doody et al, 2006;Fleige and Horn, 2000;Ibrahim et al, 2013).…”
Section: Meteorological Data Resolutionmentioning
confidence: 99%
“…Due to high soil organic carbon, it was assumed 9 that the unsaturated zone had a high attenuation capacity (Humphreys et al, 2008b). Therefore N concentrations or loads found in shallow groundwater on site do not represent losses from the agricultural system, for example from LS-0N, but instead represent transformed losses from LS-0N buffered by natural attenuation during migration through the unsaturated zone.…”
Section: Experimental Design and Descriptions Of The Dairy Systemsmentioning
confidence: 99%
“…The presence of these biochemical processes on site may have contributed to the absence of significant water quality responses. Humphreys et al (2008b) reported a lack of effect of management practices at the surface on water quality at Solohead Research Farm in 2001 and2002. Mean NO 3 --N concentrations were < 3.0 mg L -1 , not exceeding MAC limit during the experimental period and N losses to shallow groundwater were low and largely independent of N inputs, N surpluses, deposition of excreta-N at the soil surface and residual mineral N in the soil at the start of the drainage season (Humphreys et al, 2008b).…”
Section: Ammonium Nmentioning
confidence: 99%
“…environmental losses along different pathways and attenuation of such losses). Such heterogeneity influences paddock management decisions directly (Humphreys et al, 2008;Huebsch et al, 2013). Soil quality (Wilson and Maliszewska-Kordybach, 2000) is concerned with physical (the focus of the current study), chemical and biological aspects of soil across soilscapes and, therefore, defines the capacity of agricultural soil to deliver multiple functions, such as primary productivity, nutrient cycling, water filtration (Fenton et al, 2011;Jahangir et al, 2013), habitat for biodiversity and carbon sequestration (Karlen et al, 1997;Wiebe 2003;Schulte et al, 2015).…”
Section: Introductionmentioning
confidence: 99%